Sculptors, Architects, and Painters Conceive of Depicted Spaces Differently - Cialone, Claudia (Cogn Sci, 2017)
Sculptors, architects, and painters are three professional groups that require a comprehensive understanding of how to manipulate spatial structures. While it has been speculated that they may differ in the way they conceive of space due to the different professional demands, this has not been empirically tested. To achieve this, we asked architects, painters, sculptors, and a control group questions about spatially complex pictures. Verbalizations elicited were examined using cognitive discourse analysis. We found significant differences between each group. Only painters shifted consistently between 2D and 3D concepts, architects were concerned with paths and spatial physical boundedness, and sculptors produced responses that fell between architects and painters. All three differed from controls, whose verbalizations were generally less elaborate and detailed. Thus, for the case of sculptors, architects, and painters, profession appears to relate to a different spatial conceptualization manifested through a systematically contrasting way of talking about space.